Discovery of an iron instrument lately found imbedded in a natural seam of coal in the neighbourhood of Glasgow (Proceedings of the Society of Antiquaries of Scotland, 1854)
An unusual item found in a coal seam near Glasgow was exhibited and correspondence from John Buchanan regarding the find was read out. He found it odd that the item, clearly made by humans, was found encased in coal. Ultimately, it was decided by those present that the item was modern, perhaps part of a borer broken from an earlier search for coal.  The article is followed by the notes from the first conversazione of the session, held on Dec. 15, 1852. The main event from this conversazione was a lecture given by Alexander Christie on the Bayeux tapestry, including illustrations by Reverend J. Collingwood Bruce. The lecture touches on the narrative of the tapestry, before moving on to the proof of its medieval origins.